Poverty and psychological health among AIDS-orphaned children in Cape Town, South Africa. - Cluver, L; Gardner, F; Operario, D (2009)
This study examined associations between AIDS-orphanhood status, poverty indicators, and psychological problems (depression, anxiety, post-traumatic stress, peer problems, delinquency, conduct problems) among children and adolescents in townships surrounding Cape Town, South Africa. One thousand and twenty-five children and adolescents completed standardized and culturally sensitive cross-sectional surveys. Children orphaned by AIDS had more psychological problems including depression, peer problems, post-traumatic stress, and conduct problems. Specific poverty indicators including food security, access to social welfare grants, employment in the household and access to school were associated with better psychological health. Poverty indicators mediated associations of AIDS-orphanhood with psychological problems. Food security showed the most consistent association with reduced psychological problems. Poverty alleviation measures have the potential to improve psychological health for AIDS-orphaned children in South African townships.